1966
DOI: 10.1021/ie50677a011
|View full text |Cite
|
Sign up to set email alerts
|

Precise Determination of Reaction Orders

Abstract: The most commonly applied model for correlating reaction rate data is the power function rate equation, which requires careful data analysis for estimation of the reaction order. The authors present a method for the analysis of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

1967
1967
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 3 publications
0
23
0
Order By: Relevance
“…The reaction order, r, and the rate constant, kM, in the cracking step were obtained from integration of Eq. (4) by using the approach of Kittrell et al 7), and the value of r, was found to be unity. The rate constants of hydrogenation and of coke formation were evaluated from integration of Eq.…”
Section: Introductionmentioning
confidence: 77%
“…The reaction order, r, and the rate constant, kM, in the cracking step were obtained from integration of Eq. (4) by using the approach of Kittrell et al 7), and the value of r, was found to be unity. The rate constants of hydrogenation and of coke formation were evaluated from integration of Eq.…”
Section: Introductionmentioning
confidence: 77%
“…In kinetics, one type of reparameterization frequently needed is that associated with the exponential dependence of parameters upon temperature. In particular, a parameter entering many of the hyperbolic models is a rate constant such as * = y exp (-E/RT) (14) Better estimation can generally be achieved if this parameter is defined as k = y' exp ^ (15) where y' = y exp (-E/RT) (16) Now, in an estimation situation, point estimates of parameters E and y' can be obtained more readily than those of E and y using Equation 14. Compared to the direct use of Equation 14, the choice of initial parameter estimates is less critical and the estimation routine converges to the minimum more rapidly.…”
Section: Reparameterization For Surface Conditioningmentioning
confidence: 99%
“…In the determination of a reaction rate model adequately describing a heterogeneous kinetic system, one may desire to specify the functional form of a model describing his reaction system and to estimate precisely the parameters within this model. Many techniques have been developed for determining the preferred functional form of the rate model {14, 15). In this paper, we shall be primarily concerned with the estimation aspects of kinetic modeling rather than these specification aspects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of the normal distribution of the response variable i.e. y k and the possibility of outliers has been considered extensively [29,31,321. A suitable method for graphical representation of the normal distribution of data is given by Chambers et al [33].…”
mentioning
confidence: 99%